2017
DOI: 10.2185/jrm.2923
|View full text |Cite
|
Sign up to set email alerts
|

Target range of motion for rehabilitation after total knee arthroplasty

Abstract: Objective: Postoperative knee range of motion (ROM) is among the most important factors influencing patient satisfaction after total knee arthroplasty (TKA). The purpose of this study was to clarify the time course of improvement in knee ROM up to 12 months after TKA, including intraoperative knee ROM after implantation, and to clarify a target ROM for rehabilitation after TKA.Patients and Methods: In total, 39 knee joints in 26 patients with osteoarthritis who underwent TKA (retaining the posterior cruciate l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 22 publications
3
28
0
Order By: Relevance
“…Regarding knee ROM outcomes, the results of knee flexion at 6 months in both groups were comparable to those reported in other studies (97º to 116º) [ 37 ], while active knee extension values were much lower than those found in the literature [ 37 , 41 , 42 ]. This latter difference could be a result of the more demanding position used to measure knee extension—sitting as compared to lying supine—which ultimately hampered direct comparison of the results.…”
Section: Discussionsupporting
confidence: 85%
“…Regarding knee ROM outcomes, the results of knee flexion at 6 months in both groups were comparable to those reported in other studies (97º to 116º) [ 37 ], while active knee extension values were much lower than those found in the literature [ 37 , 41 , 42 ]. This latter difference could be a result of the more demanding position used to measure knee extension—sitting as compared to lying supine—which ultimately hampered direct comparison of the results.…”
Section: Discussionsupporting
confidence: 85%
“…Improvement in extension lag at week 2 implies recovery of knee extension, possibly through a potential neuromuscular mechanism [ 8 , 35 ], and might have led to an improvement in the knee extension torque in the HAL group than in the control group, which was observed at weeks 8. In a case report where a HAL-SJ was applied after TKA [ 26 ], the authors suggested that improvement in the extension lag was brought about by the HAL-SJ-mediated promotion of muscle and nerve function in the quadriceps muscle. Due to the assistance during knee motion, the extension lag during walking decreased, and it was believed that the increase in step length led to an improvement in walking speed.…”
Section: Discussionmentioning
confidence: 99%
“…The surgical procedure was similar to that described in our previous report [ 26 ]. Under general anesthesia, a midline skin incision was made, and a medial parapatellar approach was used.…”
Section: Methodsmentioning
confidence: 99%
“…Mutsuzaki et al concluded that post-operative flexion post 12 months of TKA was 113.6±15.3º in their study involving the replacement of 39 knee joints. 15 Anouchi et al showed that the post-operative flexion at 24 months was 107±10 º. This study enrolled 621 patients of whom 282 TKAs had a follow-up of 12 months and 86 have a follow-up of 24 months.…”
Section: Discussionmentioning
confidence: 97%